STANDARD ASSESSMENTS AND OUTCOME MEASURES FOR PATIENTS WITH DYSARTHRIA: A SCOPING REVIEWS STUDY - ALIAS, NORHAIZAN; MOHAMED ZAIN, NOR AZRITA; RAHMAT, SARAH; ZULKIFLI, NUR BAITI INAYAH (International Journal of Allied Health Sciences, 2023)
Apart from the basic evaluation, monitoring progress has evolved significantly over the last decade, moving away from the written treatment plan and toward a range of outcome measures and checklists. The study’s specific purpose is to ascertain the availability of assessment and patient-reported outcome measurement (PROM) tools for patients with dysarthria. The scoping review guided by Arksey & O’Malley (2005) and Peters et al., (2015) was used. Five databases were searched extensively using keywords related to dysarthria assessment and PROM (i.e., PubMed, CINAHL, ProQuest, Springer, and Scopus). Articles were screened at the title and abstract level and full text by two reviewers. One reviewer extracted data, which were then analysed descriptively to create a map of the available evidence, based on eligibility criteria (e.g., paper in English; dated 1980-February 2018; involved only real patients). Seventy-three studies met the inclusion criteria; n=26 (35.62%) utilised formal assessments for dysarthria, whereas n=47 (64.38%) used informal assessments. In terms of outcome measurement tools, 46.57 % (n=34) of studies used them, whereas 53.43% (n=39) of studies did not use any. The Assessment of the Intelligibility of Dysarthric Speech (ASSIDS) and Frenchay Dysarthria Assessment (FDA) were the two most often used assessment tools. The FDA-2 has been validated for participants with dysarthria in its European Portuguese version. The Dysarthria Impact Profile (DIP) and the Voice Handicap Index (VHI) were the most frequently used PROMs. The DIP has been validated for dysarthria patients, but not the VHI. Additionally, the DIP has been validated for dysarthria in French and European Portuguese. While the number of validated assessment and PROM tools is limited, those that are accessible have been demonstrated to have high validity and might be adapted for use in different languages.